General Biochemical Characterization of Thermostable Extracellular β-Amylase from Clostridium thermosulfurogenes - Hyun, H. H. (1985)
Clostridium thermosulfurogenes, an anaerobic bacterium which ferments starch into ethanol at 62°C, produced an active extracellular amylase and contained intracellular glucoamylase but not pullulanase activity. The extracellular amylase was purified 2.4-fold, and its general physicochemical and catalytic properties were examined. The extracellular amylase was characterized as a β-amylase (1,4-α-d-glucan maltohydrolase) based on demonstration of exocleavage activity and the production of maltose with a β-anomeric configuration from starch. The β-amylase activity was stable and optimally active at 80 and 75°C, respectively. The pH optimum for activity and the pH stability range was 5.5 to 6 and 3.5 to 6.5, respectively. The apparent [S](0.5V) and V(max) for β-amylase activity on starch was 1 mg/ml and 60 U/mg of protein. Similar to described β-amylase, the enzyme was inhibited by p-chloromercuribenzoate, Cu(2+), and Hg(2+); however, α- and β-cyclodextrins were not competitive inhibitors. The β-amylase was active and stable in the presence of air or 10% (vol/vol) ethanol. The β-amylase and glucoamylase activities enabled the organism to actively ferment raw starch in the absence of significant pullulanase or α-amylase activity.